A New Rose Bengal Glycopolymer: Photosensitization in Two Stages - Silva-Molina, C; Silva-Molina, C; Sandoval-Altamirano, C (Elsevier B.V., 2025)
Antimicrobial photodynamic therapy is a promising alternative to deal with antimicrobial resistance. However, both the low specificity and low local oxygen molecular concentrations decrease the antimicrobial efficiency limiting its use. An interesting approach to the problem is the use of molecules that can react reversibly with singlet oxygen by the formation of reversible endoperoxides, such as naphthalene, anthracene and pyridone derivatives. Particularly, the use of these molecules with mannosyl derivatives allow the interaction with adhesins presented on pili and fimbriae improving the localization near to bacteria. In this work, we synthesized polymeric nanoparticles able to generate singlet oxygen (under both irradiation and dark conditions) in the vicinity of a center capable of recognizing mannose and oxidize nearby biomolecules. Rose Bengal was used as photosensitizer due to its attractive photophysical properties (vis absorption, high singlet oxygen generation) and biocompatibility. The polymeric nanoparticles were obtained by radical polymerization using polyvinyl alcohol as a template, showing sizes around 300 nm with negative zeta potential by dynamic light scattering. The singlet oxygen generation was monitored following DPBF consumption and showed to be dependent on the amount of pyridone in the feed of polymers. In addition, the release of singlet oxygen was also dependent on pyridone concentration showing a slower rate constant at 40 % pyridone, while for contents of 10 % and 60 % higher rate constants were observed. The specific interaction of glycopolymers with Concanavalin A was demonstrated by successful agglutination assays, but also a low participation of unspecific interactions for polymers without mannosyl derivatives was observed. On the other hand, the oxidation of amino acids of Concanavalin A was monitored by acrylamide gel electrophoresis. Type I and Type II photosensitization were observed with the formation of dimers and fragments with lower molecular weight, while in dark conditions only products with lower molecular weight were observed, result consistent with singlet oxygen released by pyridone endoperoxides. © 2024 Elsevier B.V.
Keywords: Glycopolymer; Delayed singlet oxygen generation; Pyridone; Concanavalin A